Modelling and Implementation of Complex Systems Proceedings of the 5th International Symposium, MISC 2018, December 16-18, 2018, Laghouat, Algeria - Chikhi, Salim; Amine, Abdelmalek; Chaoui, Allaoua; Saidouni, Djamel Eddine (Lecture Notes in Networks and Systems, 2019)
This book presents the proceedings of the fifth International Symposium on Modelling and Implementation of Complex Systems (MISC 2018). The event was held in Laghouat, Algeria, on December 16-18, 2018. The 25 papers gathered here have been selected from 109 submissions using a strict peer-review process, and address a range of topics concerning the theory and applications of networking and distributed computing, including: cloud computing and the IoT, metaheuristics and optimization, computational intelligence, software engineering and formal methods. .